Monitoring and protection of land in the conditions of digital transformation - Butenko, Ye.; Ishchenko, N.; Mykhailyk, K. (Land Management, Cadastre and Land Monitoring, 2023)
The article analyzes the prospects for the development of monitoring of land relations, theoretical and legal aspects of its operation and trends in monitoring of relations according to existing data. In current circumstances, it is quite difficult to collect reliable monitoring data, as different areas have large areas and significant spatial and temporal characteristics. All information on land relations is collected and maintained by various departments and local authorities, and other government institutions, public organizations and individuals do not have full access to it. As a result, central authorities are not always able to see a "whole picture" of land relations, both at the district and oblast levels and at the national level, and are not always able to find optimal solutions to improve land relations. There is a need to introduce monitoring of land relations as a constantly updated information system, to ensure the accumulation of information, its analysis and forecasting, and the development of scientifically sound recommendations on this basis for effective management decisions. Proper organization of the use of monitoring information will make it possible to assess the quantitative and qualitative indicators of the state of lands, and to assess and forecast changes. The issue of lack of free access to information on land relations, which creates favorable conditions for land use improperly, evasion of compliance with the requirements of land and environmental legislation of Ukraine, the spread of corruption. Today, all information on land relations is collected and maintained by various departments and local authorities, and other government institutions, public organizations and individuals do not have full access to it. As a result, central authorities do not always have the opportunity to see a "holistic picture" of land relations, both at the district and oblast levels, and at the national level, and do not always have the opportunity to find optimal solutions to improve land relations. The need to create a constantly updated database on the state of development of land relations, with open access for monitoring entities as an integrating information network, as well as for forecasting and control of rational land use, and ensuring transparency in land relations management. The creation of such a base will focus on the effectiveness of management decisions and improve the management of land use in general. Keywords: digital transformation, land monitoring; land relations monitoring; land resources; land use; land relations.